2011
DOI: 10.18352/ulr.147
|View full text |Cite
|
Sign up to set email alerts
|

Research on the caseload management of courts: methodological questions

Abstract: This article is published in a peer-reviewed section of the Utrecht Law Review

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The limited data hinders, for example, the investigation of whether different types of caseload influence judicial performance, or whether different types of administrative assistants influence the relationship between caseload and judge production. Or even whether other variables and indicators of judicial performance should be used, in addition to the production of sentences and hearings by judges (For methodological issues on court caseload management, see Lienhard & Kettiger, 2011). Future studies could investigate other possible intervening variables through qualitative studies, using as data collection, for example, interviews and focus groups.…”
Section: Discussionmentioning
confidence: 99%
“…The limited data hinders, for example, the investigation of whether different types of caseload influence judicial performance, or whether different types of administrative assistants influence the relationship between caseload and judge production. Or even whether other variables and indicators of judicial performance should be used, in addition to the production of sentences and hearings by judges (For methodological issues on court caseload management, see Lienhard & Kettiger, 2011). Future studies could investigate other possible intervening variables through qualitative studies, using as data collection, for example, interviews and focus groups.…”
Section: Discussionmentioning
confidence: 99%
“…9 Some studies have found that in the relationship between gender and mediation judgment rate, most female judges have higher mediation withdrawal rate and lower mediation withdrawal enforcement rate than more male judges. 10 However, the topic of this paper is to explore whether the gender of judges may affect the mediation efficiency.…”
Section: Gendermentioning
confidence: 99%
“…Although the study offers no "recipe" on how to conduct a CWA, the long list of references could provide more information (and details such as time logs, software, and so on). Leinhard, Andreas, and Daniel Kettiger. 2011 Ketterle, below), the authors' preferred method is to measure the average time per case rather than to use an events-based approach.…”
Section: Box 13 What a Cwa And Related Efficiency Approaches Can Andmentioning
confidence: 99%